If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + a = -3c + 44 Reorder the terms: a + 2c = -3c + 44 Reorder the terms: a + 2c = 44 + -3c Solving a + 2c = 44 + -3c Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2c' to each side of the equation. a + 2c + -2c = 44 + -3c + -2c Combine like terms: 2c + -2c = 0 a + 0 = 44 + -3c + -2c a = 44 + -3c + -2c Combine like terms: -3c + -2c = -5c a = 44 + -5c Simplifying a = 44 + -5c
| 2z+5+3z=10 | | -5x^2+15x-9=0 | | -3[r+4]=21 | | -5w(w-3)(w+2)=0 | | -3[r+4]=-21 | | 5[q+6]=-20 | | 5[q+6]=20 | | 8x-9=33-4x | | 5x+7=2x-9 | | -3(-4-6x)=84 | | x^3+2x^2+4=0 | | -y+3z=9 | | 12+18x=84 | | 2+18x=84 | | 6x-6x=-2 | | 3x^3-6x^2-45x=0 | | 7k^2+6k-1=0 | | 5-(3n+5)=3-(7n+3) | | 14m+4n-6m+11n= | | 6n^2-14+8=0 | | 3(u-3)=2(x+5) | | [b+5]=2b+3 | | 15x^2-61x+53=-3 | | -2[5y-1]=-10 | | x^2+5x+62.5=0 | | 4x^2-29x-23=1 | | 2x+5(7)= | | 16x-16=5+x | | 1-6(1+3r)=-113 | | 42x^2+31x-19=2 | | 8x+6=180 | | (25ln(5)-23ln(0))-(25ln(2)-23ln(3))=x |